Comparative Analysis of Physico-Chemical Properties of Oil Extract From Two Varieties of Fluted Pumpkin Seeds Using Different Extraction Methods - Sunmonu, M. O.; Ajala, E. O.; Odewole, M. M.; Morrison, S.; Alabi, A. M. (Kathmandu University Journal of Science, Engineering and Technology, 2018)
This study investigates physical and chemical properties two seeds namely Ugba (Telfairia pedata) and Ugwu (Telfairia occidentalis) using soaking soxhlet methods of extraction. The physical properties examined are moisture content, ash content, crude protein, fat and oil, crude fibre and carbohydrates. The chemical properties examined are Acid value (mgKOH/g), saponification value, iodine value, free fatty acid, peroxide and refractive index. Higher mean values of moisture content, ash content, crude fibre and carbohydrates were noticed in Ugwu than in Ugba under soaking method. However, the trend was reversed for crude protein and free fatty acid, in whose case they appear to be higher in Ugba than in Ugwu. For soxhlet method, moisture content, ash content, crude fibre and carbohydrates seems to have higher mean values in Ugwu seed compared to when Ugba seed was used. However, crude protein and fat and oil content were higher using Ugba seed than Ugwu seed oil. For soaking method, Ugba seed seem to produce higher mean values of sap value, iodine value, and refractive index when compared with Ugwu seed. On the other Ugwu, seems to produce acid value, free fatty acid and peroxide value when compared with ugba for soaking method. Using soxhlet apparatus however, Ugba seed produces higher mean values for acid value, sap value, iodine value, and free fatty acid compared to Ugwu. The reverse was the case with peroxide and refractive index, still with soxhlet apparatus.Kathmandu University Journal of Science, Engineering and TechnologyVol. 13, No. 2, 2017, page: 48-60